Pemberdayaan Remaja dalam Pencegahan HIV/AIDS melaui Life Skill Education di Kabupaten Tuban - Nugraheni, Wahyuningsih Triana; Yunariyah, Binti; Su'udi, Su'udi (Universitas Pahlawan Tuanku Tambusai, 2025)
Adolescents face highly complex problems. Emotional and psychological pressures can lead to deviations from prevailing social norms in the community, such as environmental issues, reproductive health concerns, promiscuous sexual behavior, abortion, and sexually transmitted diseases, including HIV/AIDS. The number of HIV cases in Tuban Regency increased from 53 cases in 2021 to 163 cases in 2022. The aim of this community service program is to improve adolescents’ knowledge and life skills in preventing HIV/AIDS. The methods used included lectures, discussions, games, assignments, and demonstrations, targeting adolescents in Kembangbilo Village, Tuban Regency. The results showed that the average knowledge score on HIV/AIDS prevention life skills before the educational intervention was 42.6, increasing to 65 after the intervention. The average life skills score for HIV/AIDS prevention before the intervention was 53.5, increasing to 68.5 afterward. Empowering adolescent peer educators proved to be highly effective in enhancing life skills for HIV/AIDS prevention. In this era of advanced communication systems, it is crucial to equip adolescents with life skills to prevent HIV/AIDS.